Effects of vision impairment on cognitive function: the bidirectional chain mediating role of sleep quality and psychological disorders - Yu, Minghao; Zhou, Hangqing; Zhao, Yi; Lu, Hanna; Shao, Yan (Frontiers in Public Health, 2025)
IntroductionVision impairment (VI) and cognitive function have profound impacts on quality of life, but there is still a lack of comprehensive research on the connection between VI and cognitive function. The study was designed to investigate factors influencing cognitive function, analyze the link between VI and cognitive function, and explore how sleep quality and psychological disorders mediate this relationship.MethodsThe study utilizes survey data from the Health and Retirement Study (HRS) involving 10,884 older adults aged 50 and above in the United States. Pearson correlation analysis was conducted to elucidate the associations between the variables, and the R package bruceR (version 2024.6) was used to analyze multiple mediation effects through model 6.ResultsVI is positively correlated with sleep quality and psychological disorders, and negatively correlated with cognitive function. Sleep quality is positively correlated with psychological disorders and negatively correlated with cognitive function. Psychological disorders are negatively correlated with cognitive function. All correlations are statistically significant. VI directly impacts cognitive function while also indirectly influencing it through sleep quality, psychological disorders, and the bidirectional mediating chain connecting these factors.ConclusionSleep quality, psychological disorders, and their bidirectional relationships mediate the effect of VI on cognitive function in aging populations. Through this study, we gain a more profound comprehension of how VI relates to cognitive function. In the future, cognitive enhancement in individuals with VI could be achieved by improving sleep quality, addressing psychological disorders, or integrating assessments of these factors into the evaluation of cognitive function.